Role of Online Journalism in Interactive Communication (Herald of Journalism, 2016)
This study was carried out on the interactive internet sites role in the communication among the youth during 2012. The applied study was on Sudanese Online site.This research used historical method and questionnaire for data collec-tion. The questionnaire was distributed among Sudanese Online visitors as a sample of 140 persons.The most important findings of this study were that most of the sample was who visit interactive internet sites were young people; they visit these sites for looking for information besides educational programs and the most preferred interactive site for the visitors was Sudanese Online.
Keywords: Key words; Sudanese Online site; interactive internet sites; role in the communication; educational programs.